Piano Trios op. 1, nos. 1-3 (Carli) - Beethoven, Ludwig van, 1770-1827 (composer):::Creator::: (France; Paris; Carli, 2024)
Early edition of the Piano Trios in E-flat major, G major, and C minor, op. 1, nos. 1-3, published by Carli.